Evolving Trends and Risk Factors in Infectious Keratitis after Keratoplasty: A 22-Year Multi-Institutional Analysis - Yueh-Ling Chen; Ching-Hsi Hsiao; David Hui-Kang Ma; Yi-Jen Hsueh; Lung-Kun Yeh; Hsin-Yuan Tan; Kuo-Hsuan Hung; Hung-Chi Chen (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. To analyze the incidence, risk factors, and microbial profiles of infectious keratitis after different types of keratoplasty, we conducted a retrospective multi-institutional study using the Chang Gung Research Database in Taiwan and included keratoplasty cases between January 2001 and December 2022. Procedural codes were used to identify keratoplasty cases, and infectious keratitis was confirmed by positive culture results. Outcomes included the incidence of infectious keratitis after penetrating keratoplasty, anterior lamellar keratoplasty, and endothelial keratoplasty as well as associated pathogens and risk factors. Logistic regression analysis was performed to identify significant risk factors, including age, surgical technique, and systemic and ocular conditions. In total, 297 patients with infectious keratitis after keratoplasty were identified. The percentage of infectious keratitis within 1 year after keratoplasty increased from 7.7% in 2001–2011 to 14.0% in 2012–2022, with the highest rates observed after anterior lamellar keratoplasty followed by penetrating keratoplasty and endothelial keratoplasty. Older age, ocular surface diseases, and anterior lamellar keratoplasty were significant risk factors. Gram-positive bacteria, particularly Staphylococcus species, were the most commonly isolated pathogens, whereas Pseudomonas aeruginosa was the predominant Gram-negative bacterium. Fusarium and Candida species were the leading fungal pathogens, and viral pathogens, including cytomegalovirus and Epstein–Barr virus, were identified in a small subset. In conclusion, the incidence of infectious keratitis after keratoplasty has increased over time ( P